Risk of Recurrence of Chronic Subdural Hematomas After Surgery: A Multicenter Observational Cohort Study - Cofano, Fabio; Pesce, Alessandro; Vercelli, Giovanni; Mammi, Marco; Massara, Armando; Minardi, Massimiliano; Palmieri, Mauro; D'Andrea, Giancarlo; Fronda, Chiara; Lanotte, Michele Maria; Tartara, Fulvio; Zenga, Francesco; et al. (Frontiers in Neurology, 2020)
Background Chronic Subdural Hematoma (CSDH) is a common condition in the elderly population. Recurrence rates after surgical evacuation range from 5% to 30%. Factors predicting recurrence remain debated and unclear. Objective To identify factors associated with increased risk of recurrence. Methods Cases of CSDHs that underwent surgical treatment between 2005 and 2018 in the Neurosurgery Units of two major Italian hospitals were reviewed. Data extracted from a prospectively maintained database included demographics, laterality, antithrombotic therapy, history of trauma, corticosteroid therapy, preoperative and postoperative symptoms, type of surgical intervention, use of surgical drain, and clinical outcomes. Results A total of 1313 patients was analyzed. The overall recurrence rate was 10.1%. The risk of recurrence was not significantly different between patients with unilateral or bilateral CSDH (10.4% vs 8.8%, p = 0.39). The risk of recurrence was higher in patients that underwent surgical procedure without postoperative drainage (16.1% vs 5.4%, p < 0.01). No relationship was found between recurrence rates and therapy with antithrombotic drugs (p = 0.97). The risk of recurrence was increasingly higher considering craniostomy, craniectomy, and craniotomy (9.3%, 11.3% and 18.9% respectively, p = 0.013). Lower recurrence rates following Dexamethasone therapy were recorded (p = 0.013). Conclusion No association was found between the risk of recurrence of CSDH after surgical evacuation and age, use of antithrombotic medication, or laterality. Burr-hole craniostomy was found to be associated with lower recurrence rates, when compared to other surgical procedures. Placement of surgical drain and Dexamethasone therapy were significantly associated with reduced risk of recurrence of CSDHs.